Pengembangan Aplikasi Pengelolaan Transaksi Warung berbasis Web untuk Tini Mart - Azhari Arsyad; Ismiarta Aknuranda; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
In the trade sector, transaction management is crucial because if transactions are not managed properly, they can cause considerable losses. This risk is also found in a shop called Tini Mart. Transaction management at these stalls is still traditional, such as providing prices by remembering the price of goods and manually calculating the total price and change. This method has many risks such as giving the wrong price, calculating the total price incorrectly, and giving the wrong amount of change. This can cause losses to the shop and decrease the confidence of buyers in the shop. Now there are several transaction management applications on the market that are freely available but are not suitable for use in Tini Mart. This is because there are functional requirements, such as debt management, and non-functional requirements, such as supporting the interface on a large screen and having a simple, easy-to-understand interface and navigation for users, which are still not met. Therefore, this research was conducted with the aim of developing applications that can meet the requirements that have not been met previously. This application development process model will use the waterfall. The application is built using the Laravel framework with the JavaScript and PHP programming languages. The test results state that all functional requirements of the application have been met because it has a 100% success rate and all non-functional requirements of the application have been met because after observations and interviews there were no obstacles and users can easily use the application.